2007
DOI: 10.1016/j.susc.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of reflection electron energy loss spectra (REELS) for determination of the dielectric function of solids: Fe, Co, Ni

Abstract: A simple procedure is developed to simultaneously eliminate multiple scattering contributions from two reflection electron energy loss spectra (REELS) measured at different energies or for different experimental geometrical configurations. The procedure provides the differential inverse inelastic mean free path (DIIMFP) and the differential surface excitation probability (DSEP).The only required input parameters are the differential cross section for elastic scattering and a reasonable estimate for the inelast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Deviations from Palik's data were also reported by Werner. 28 In Ref. 21 it was found that the Yubero-Tougaard theory gives a good agreement with experimental effective cross sections determined by the Tougaard-Chorkendorff algorithm for a very wide range of geometries (35 -74 off normal), and energies 200, 500, and 1000 eV for several materials (Cu, Ag, Au, and Fe) all obtained with the same e(k,x) for each material.…”
Section: Introductionmentioning
confidence: 68%
“…Deviations from Palik's data were also reported by Werner. 28 In Ref. 21 it was found that the Yubero-Tougaard theory gives a good agreement with experimental effective cross sections determined by the Tougaard-Chorkendorff algorithm for a very wide range of geometries (35 -74 off normal), and energies 200, 500, and 1000 eV for several materials (Cu, Ag, Au, and Fe) all obtained with the same e(k,x) for each material.…”
Section: Introductionmentioning
confidence: 68%
“…The accuracy with which these quantities are known determines the reliability of the procedure for restoration of the differential inelas tic scattering cross sections from experiments deter mining the characteristic electron energy losses [17,18].…”
Section: Discussion and Approbation Of The Obtained Resultsmentioning
confidence: 99%
“…Firstly, the Monte Carlo (MC) simulation, that incorporates all physical phenomena governing the random path of the electrons and allows to reproduce the full REELS spectra, is a convenient way of comparison . Secondly, comparison between cross sections obtained from theoretical calculation and from REELS experiment is also a straightforward way to validate theories. From these two methods, excellent results have been achieved by different groups for various studied materials (see other works, for instance).…”
Section: Introductionmentioning
confidence: 89%